Propuesta de reingeniería del centro de datos del Instituto Nacional de Aprendizaje - Brenes-Granados, Milagro (Instituto Tecnológico de Costa Rica, 2014)
The following Project consists in giving a reengineering proposal from the data center at Instituto Nacional de Aprendizaje (National Institute for Learning, INA initials in Spanish), which is an autonomous Costa Rican institution that gives training and professional services to people older than 15 years old and also to corporations. The proposal is based on standards and regulations emitted by the ANSI/BICSI Norm from the American National Standards Institute (ANSI), and TIA 942 Norm; which has been approved by TIA (Telecommunications Industry Association) and ANSI; as well as the directions and autonomous procedures of the institution. The re-structuring is specifically based on four systems, which are the architectural system, telecommunications system, mechanical system, and electrical system. On the first section, it is developed all the information related to the project regarding to general information, background, problem definition, justification, and objectives. The second section is oriented to describe the principal regulations, standards and good practices for a data center design according to different levels of availability and reliability that may be implemented. On the third section, it is carried out the methodology used to start the project; for example, it is found the type of research, the information sources, methodology used, instruments, among others. On the fourth section, it is pointed out in a detailed form, the real situation by which the data center is currently working, taking into account the physical architecture, net architecture, mechanical system, electrical system, cooling system, and security system; allowing to define the actual requirements and weaknesses, to be able to develop the reengineering proposal. On the fifth section, it is unrolled the reengineering proposal is developed for the data center from the Instituto Nacional de Aprendizaje, based on the needs and deficiencies analyzed on the previous sections; as well as the definition of a plan for costs management and a plan of logical operation, that permits to count on the needed income to reduce to the minimum the probability to fall into a fail in the service given by the data center to the processes in the whole institution at the national level. To finish, it is presented the conclusions and recommendations obtained from the developed project, also the annexes which give support to all the development.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2014.
Keywords: Gestión de proyectos; Diseño; Normalización; Telecomunicaciones; Gestión financiera